Improved Production of Aspergillus usamii endo-β-1,4-Xylanase in Pichia pastoris via Combined Strategies. - Wang, Jianrong; Li, Yangyuan; Liu, Danni (BioMed Research International, 2016)
A series of strategies were applied to improve expression level of recombinant endo-β-1,4-xylanase from Aspergillus usamii (A. usamii) in Pichia pastoris (P. pastoris). Firstly, the endo-β-1,4-xylanase (xynB) gene from A. usamii was optimized for P. pastoris and expressed in P. pastoris. The maximum xylanase activity of optimized (xynB-opt) gene was 33500 U/mL after methanol induction for 144 h in 50 L bioreactor, which was 59% higher than that by wild-type (xynB) gene. To further increase the expression of xynB-opt, the Vitreoscilla hemoglobin (VHb) gene was transformed to the recombinant strain containing xynB-opt. The results showed that recombinant strain harboring the xynB-opt and VHb (named X33/xynB-opt-VHb) displayed higher biomass, cell viability, and xylanase activity. The maximum xylanase activity of X33/xynB-opt-VHb in 50 L bioreactor was 45225 U/mL, which was 35% and 115% higher than that by optimized (xynB-opt) gene and wild-type (xynB) gene. Finally, the induction temperature of X33/xynB-opt-VHb was optimized in 50 L bioreactor. The maximum xylanase activity of X33/xynB-opt-VHb reached 58792 U/mL when the induction temperature was 22°C. The results presented here will greatly contribute to improving the production of recombinant proteins in P. pastoris.